ECONOMIC VALUATION ESTIMATION OF SUPPLEMENTARY IRRIGATION WATER IN CROP FARMING ENTERPRISES IN BANTUL REGENCY - Khafid, Mohammad Abdul; Syaukat, Yusman; Kusmana, Cecep (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
Hydrological droughts in Bantul Regency significantly reduce crop productivity to an average of 59.97 kw/ha, thereby affecting farmers' income due to land conversion and water scarcity. This study evaluates the economic implications of supplementary irrigation in high, moderate, and low drought-prone zones. Farmers in low (Sabdodadi) and moderate (Guwosari) drought-prone areas can cultivate rice twice a year, whereas those in high drought-prone areas (Wukirsari) can do so only once. The methods employed include literature review, field survey, field data collection, and data analysis using RIA (Residual Imputation Approach) and ArcGIS 10.8. Cash costs for the third planting season in Sabdodadi, Guwosari, and Wukirsari amounted to Rp 11,590,451, Rp 11,698,165, and Rp 10,671,432 per hectare, respectively. Non-cash costs were Rp 2,600,260, Rp 3,331,483, and Rp 4,229,162 per hectare. Total production costs fluctuated, particularly in Sabdodadi, totaling Rp 14,190,711 per hectare. Sabdodadi exhibited the highest income at Rp 15,518,964 per hectare, while Guwosari and Wukirsari reached Rp 15,778,358 and Rp 14,778,346 per hectare. Supplementary irrigation significantly enhances the economic value of food crops, ranging from 20% to 29.15%, with Wukirsari making the highest contribution. The strategy of implementing flexible water tariffs and developing irrigation infrastructure can be applied to promote economic growth in drought-prone areas. Empowering farmers through economic incentives and access to adequate irrigation water is expected to create conditions conducive to sustainable agriculture.